Zorotypus huangi sp. nov. (Zoraptera: Zorotypidae) from Yunnan, southern China - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2017)
A new species of the insect order Zoraptera, Zorotypus huangi Yin & Li, sp. nov., is described based on apterous adults collected from Yunnan, southern China. The new species differs from the previously described Chinese congeners primarily in possessing a different type of the aedeagus, whereas it shows affinities to the Malaysian Z. impolitus and Z. weiweii. This discovery highlights the diversity and complexity of the zorapteran fauna in China, and indicates that more species are likely to be found in suitable habitats along the state’s southwest border.